(untitled) (Journal of EAHIL, 2018)
Introducing best available information sources and services to specialists starting in a new position is one of the tasks of Information Services in Orion Corporation. We developed a deck of cards to help us in finding out training attendants’ information needs and to personalize the training. In this paper we describe the process of creating the cards and how they are used in our training. We also share results of an attendant survey and address other outcomes of the project.